RESPON TANAMAN PADI GOGO VARIETAS SITU BAGENDIT DENGAN BERBAGAI METODE PENGELOLAAN PUPUK KANDANG - Nurseha Nurseha; Danner Sagala; Helmi Rajab (University of Prof. Dr. Hazairin, SH, 2012)
This study was aimed to find the effect of various methods of manure management and to determine the best method on growth and production of highland rice Situ Bagendit variety. The reseach was conducted in the Rimbo Kedui Village South Seluma District Seluma regerency from February to June 2011. This study was arranged in randomized block design to examine the 5 treatments with 4 replications. The treatments studied were synthesis fertilizer, manure+sand, manure+husk, Bokashi, and manure only. Result showed that the various methods of manure management cignificantly affected all of variables except plant heiglat on 8 weeks after planting/wap, shoot number on 6 and 8 wap, and biomas dry weight. organic fertilizer was better than synthetic fertilizer. However the various methods of manure management gave efferent effect to the growth and yield. Bokashi method was the best treasure which can push the rice to produce 4.126 kg.ha-1.